A Crosslinked Polytetrahydrofuran‐Borate‐Based Polymer Electrolyte Enabling Wide‐Working‐Temperature‐Range Rechargeable Magnesium Batteries. Issue 11 (23rd January 2019) - Du, Aobing; Zhang, Huanrui; Zhang, Zhonghua; Zhao, Jingwen; Cui, Zili; Zhao, Yimin; Dong, Shanmu; Wang, Longlong; Zhou, Xinhong; Cui, Guanglei
Abstract: A polymer‐based magnesium (Mg) electrolyte is vital for boosting the development of high‐safety and flexible Mg batteries by virtue of its enormous advantages, such as significantly improved safety, potentially high energy density, ease of fabrication, and structural flexibility. Herein, a novel polytetrahydrofuran‐borate‐based gel polymer electrolyte coupling with glass fiber is synthesized via an in situ crosslinking reaction of magnesium borohydride [Mg(BH4 )2 ] and hydroxyl‐terminated polytetrahydrofuran. This gel polymer electrolyte exhibits reversible Mg plating/stripping performance, high Mg‐ion conductivity, and remarkable Mg‐ion transfer number. The Mo6 S8 /Mg batteries assembled with this gel polymer electrolyte not only work well at wide temperature range (−20 to 60 °C) but also display unprecedented improvements in safety issues without suffering from internal short‐circuit failure even after a cutting test. This in situ crosslinking approach toward exploiting the Mg‐polymer electrolyte provides a promising strategy for achieving large‐scale application of Mg‐metal batteries. Abstract : A novel polytetrahydrofuran‐borate‐based gel polymer electrolyte coupling with glass fiber (PTB@GF‐GPE) is synthesized via an in situ crosslinking reaction of magnesium borohydride and hydroxyl‐terminated poly(tetrahydrofuran). The Mo6 S8 //PTHF@GF‐GPE//Mg batteries exhibit outstanding electrochemical performance at the range of 60 to −20 °C and display prominent safety characteristics with a good internal short‐circuit prevention.